Features of capsule endoscopy in COVID‐19 patients with a six‐month follow‐up: A prospective observational study. Issue 1 (10th September 2021) - Xie, Xiao‐Ping; Sheng, Li‐Ping; Han, Chao‐Qun; Jin, Yu; Bai, Tao; Lin, Rong; Ding, Zhen; Hou, Xiao‐Hua
Abstract: Recently, the coronavirus disease 2019 (COVID‐19) has caused a global pandemic. Several studies indicate that the digestive system can also be affected by the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). Therefore, patients with digestive symptoms should have a capsule endoscopy (CE). COVID‐19 patients with gastrointestinal (GI) symptoms who underwent CE were recruited from March 2020 to April 2020. We collected patients' data and performed a prospective follow‐up study for 6 months. All 11 COVID‐19 cases with GI symptoms who underwent CE presented gastritis. Eight cases (72.7%) had intestinal mucosa inflammation. Among them, two cases showed intestinal ulcers or erosions. Moreover, two cases displayed colonic mucositis. One case was lost during follow‐up. At 3–6 months after hospital discharge, five patients underwent CE again, presenting gastrointestinal lesions. Five of the 10 cases had GI symptoms, such as abdominal pain, diarrhea, constipation, and others. Among these five cases, the GI symptoms of three patients disappeared at the last follow‐up and two patients still presented diarrhea symptoms. Overall, we observed damaged digestive tract mucosa that could be caused by SARS‐CoV‐2. Moreover, after discharge, some patients still presented intestinal lesions and GI symptoms.